2021
DOI: 10.1097/mcc.0000000000000859
|View full text |Cite
|
Sign up to set email alerts
|

The impact of resource limitations on care delivery and outcomes: routine variation, the coronavirus disease 2019 pandemic, and persistent shortage

Abstract: Purpose of review Resource limitation, or capacity strain, has been associated with changes in care delivery, and in some cases, poorer outcomes among critically ill patients. This may result from normal variation in strain on available resources, chronic strain in persistently under-resourced settings, and less commonly because of acute surges in demand, as seen during the coronavirus disease 2019 (COVID-19) pandemic. Recent findings Recent studies confirmed existing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…A shorter ventilator time and ICU stay were particularly valuable during the COVID-19 pandemic, when intensive care units (ICUs) had insufficient ventilator and beds [ 12 ]. Tracheostomy was considered an attractive intervention to potentially reduce the time on a ventilator, length of ICU stay, and mortality [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A shorter ventilator time and ICU stay were particularly valuable during the COVID-19 pandemic, when intensive care units (ICUs) had insufficient ventilator and beds [ 12 ]. Tracheostomy was considered an attractive intervention to potentially reduce the time on a ventilator, length of ICU stay, and mortality [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although additional beds and facilities for critically ill COVID-19 patients were gradually provided, the number of ICU beds for non-COVID-19 patients decreased by 10 to 15 in each hospital included in this study during the study period. Furthermore, intensivists and critical care nurses were insufficient in number and difficult to recruit; therefore, the workload of these experienced practitioners increased [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The disruption in staff, equipment, and space contribute to complex interactions affecting patient care and outcomes. 79 Capacity strain includes patient census and volume, turnover, acuity and workload. 79 Care of the critically ill patient requires a multidisciplinary team of clinicians which can be challenging to replicate outside of traditional ICU settings when space becomes limited.…”
Section: Introductionmentioning
confidence: 99%
“… 79 Capacity strain includes patient census and volume, turnover, acuity and workload. 79 Care of the critically ill patient requires a multidisciplinary team of clinicians which can be challenging to replicate outside of traditional ICU settings when space becomes limited. Observational studies have demonstrated a relationship between strain on ICU resources and ICU patient outcomes.…”
Section: Introductionmentioning
confidence: 99%